A neural approach for determination of global energetic efficiency indicator in groundwater wells - Saggioro, Nilton Jose [UNESP]; Cagnon, Jose Angelo [UNESP]; Nunes Da Silva, Ivan [UNESP] (My University, 2002)
In most of the cases, the systems of water distribution from groundwater wells use electrical submersible pumps. All electrical energy is applied to the pumps; however, other components (pipes, valves, etc.) of these systems are also responsible by the higher or lower consumption of electric energy. The supervisors and operators of the systems should thus have knowledge of the global energetic behavior of the process in order to administrate it properly. This work suggests a 'Global Energetic Efficiency Indicator' for groundwater wells by using mathematical equations and neural networks. Simulation results will be presented in order to demonstrate the validity of the proposed approach.